Augmentation of bursting pacemaker activity by egg-laying hormone in Aplysia neuron R15 is mediated by a cyclic AMP-dependent increase in Ca2+ and K+ currents. - Levitan, E S (1987)
Release of the neuropeptide egg-laying hormone (ELH) from Aplysia bag cell neurons augments the endogenous bursting pacemaker activity of neuron R15. We have studied the ionic mechanisms underlying the effect of ELH in voltage-clamped R15 neurons. Both electrical discharge of the bag cells, which releases endogenous ELH, and application of synthetic ELH on cell R15 result in an increase in two discrete ionic currents. One of these currents activates with hyperpolarization, reverses near the K+ equilibrium potential, is sensitive to the external K+ concentration, and is blocked by addition of 5 mM Rb+ or 1 mM Ba2+ to the bathing medium. This current appears to be identical to the inwardly rectifying K+ current IR. The other current activates with depolarization and is blocked by replacement of external Ca2+ with Co2+ or Mn2+. This current appears to be a voltage-gated Ca2+ current ICa. Both ICa and IR in R15 have previously been shown to be enhanced by the neurotransmitter serotonin, acting via intracellular cyclic AMP. We now report that increasing cyclic AMP in R15, by applying either serotonin or the adenylate cyclase activator forskolin together with a phosphodiesterase inhibitor, mimics and occludes the action of ELH on neuron R15. Furthermore, application of ELH increases the cyclic AMP content of single R15 neurons, as measured by radioimmunoassay. Finally, the effects of ELH are potentiated by a phosphodiesterase inhibitor. These results suggest that ELH augments bursting activity in R15 by causing cyclic AMP-mediated increases in IR and ICa.